El mundo interno, el imaginario y la política - Carrillo Zapata, Ricardo; Saibacam, Jacobo (Foro Interno, 2010)
This article analyzes the concomitant relationship between the notions of imaginary in Cornelius Castoriadis and of internal world in Hannah Arendt. These two theoretical constructs have extended the sphere of politics, providing a deeper knowledge of the citizen’s self. these authors, who were contemporaries of each other, diagnose in their works a hypertrophy of the identity logic due to fear of losing control and to anguish in the face of contingency, resulting in the idolatrous solution of omnipotence in the political sphere. Castoriadis and Arendt discover instead a richer understanding of liberty through the recognition of democracy in the inner forum. their political theories echo the mediterranean rhetorical tradition and shine light on some of the most prominent deformations of Western thought, evident in thinkers such as Thomas Hobbes.
Keywords: Castoriadis; Arendt; Imaginary; Internal world; Identity logic; Rhetorical tradition